2014
DOI: 10.1590/bjpt-rbf.2014.0053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single session of transcranial direct-current stimulation on balance and spatiotemporal gait variables in children with cerebral palsy: A randomized sham-controlled study

Abstract: Background: Transcranial direct-current stimulation (tDCS) has been widely studied with the aim of enhancing local synaptic efficacy and modulating the electrical activity of the cortex in patients with neurological disorders. Objective: The purpose of the present study was to determine the effect of a single session of tDCS regarding immediate changes in spatiotemporal gait and oscillations of the center of pressure (30 seconds) in children with cerebral palsy (CP). Method:A randomized controlled trial with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 26 publications
1
39
0
8
Order By: Relevance
“…The findings of the current study supported this hypothesis and indicated that participants who received cerebellar a‐tDCS had significantly less postural sway in AP and ML directions in the static conditions, which means a better static postural control. Due to lack of comparable studies in the literature, the findings in the current study will only be compared with a‐tDCS studies which investigated static postural stability of the individuals with postural disorders (Duarte et al ., ; Grecco et al ., ; Dumont et al ., ). In line with the findings in the current study, literature supports positive effect of a‐tDCS of M1 on the static postural control (Duarte et al ., ; Grecco et al ., ; Dumont et al ., ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The findings of the current study supported this hypothesis and indicated that participants who received cerebellar a‐tDCS had significantly less postural sway in AP and ML directions in the static conditions, which means a better static postural control. Due to lack of comparable studies in the literature, the findings in the current study will only be compared with a‐tDCS studies which investigated static postural stability of the individuals with postural disorders (Duarte et al ., ; Grecco et al ., ; Dumont et al ., ). In line with the findings in the current study, literature supports positive effect of a‐tDCS of M1 on the static postural control (Duarte et al ., ; Grecco et al ., ; Dumont et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Participants were asked to randomly stand on the static and dynamic platforms of BBS and maintain balance for 30 s (Sherafat et al ., ; Ehsani et al ., ,b). After performing balance tests and saving the BBS baseline data, participants were asked to sit on a chair to receive a‐tDCS intervention for 20 min (Grecco et al ., ). Then, the balance assessments by BBS were randomly repeated immediately after the intervention to obtain BBS intervention data.…”
Section: Methodsmentioning
confidence: 97%
“…29 30 Moreover, a non-invasive brain stimulation method (tDCS) will be employed to facilitate motor cortical excitability in the areas subjacent to stimulation to enhance the effects of motor control and learning. [37][38][39][40][41][42] Lazzari et al 37 demonstrated the efficacy of the combination of tDCS and VR in potentiating motor effects on balance and functional mobility in children with cerebral palsy. 37 This document offers a detailed description of a randomised, controlled, double-blind, clinical trial designed to determine the effectiveness of VR training combined with tDCS on upper limb movements in individuals with DS.…”
Section: Discussionmentioning
confidence: 99%
“…The results of clinical trials have demonstrated its considerable potential in the treatment of neurological disorders and the investigation of processes of cortical excitability modulation. [37][38][39][40][41][42] Moreover, this type of intervention offers a better condition for sham stimulation, which confers greater specificity to the findings. 39 40 In the rehabilitation process, the aim of neuromodulating techniques is to enhance local synaptic efficiency and alter the maladaptive plasticity pattern that emerges after a cortical injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation